Characterization of a submicro‐X‐ray fluorescence setup on the B16 beamline at Diamond Light Source. (13th June 2018) - Rauwolf, M.; Turyanskaya, A.; Ingerle, D.; Szoboszlai, N.; Pape, I.; Malandain, A. W.; Fox, O. J. L.; Hahn, L.; Sawhney, K. J. S.; Streli, C.
Abstract : The use of the X‐ray fluorescence setup on the B16 beamline at the Diamond Light Source for X‐ray imaging with sub‐micrometer resolution was described and it was shown that this setup is very well suited for studying thin samples, especially for biological applications. Abstract : An X‐ray fluorescence setup has been tested on the B16 beamline at the Diamond Light Source synchrotron with two different excitation energies (12.7 and 17 keV). This setup allows the scanning of thin samples (thicknesses up to several micrometers) with a sub‐micrometer resolution (beam size of 500 nm × 600 nm determined with a 50 µm Au wire). Sensitivities and detection limits reaching values of 249 counts s −1 fg −1 and 4 ag in 1000 s, respectively (for As K α excited with 17 keV), are presented in order to demonstrate the capabilities of this setup. Sample measurements of a human bone and a single cell performed at B16 are presented in order to illustrate the suitability of the setup in biological applications.